Test-bedding of chilled ceiling in JTC summit building - Ng, Gim Wei (2014)
The Chilled Ceiling has been widely used in Europe for decades and has proven to provide thermal comfort and energy savings compared to conventional air-conditioning systems. However, the performance of this technology has yet to be verified in Singapore to substantiate the feasibility for use locally. The aim of this project is to verify the performance and financial feasibility of the Chilled Ceiling in Singapore. A test bed would be conducted in JTC Summit building where one of the meeting rooms would be retrofitted with the Chilled Ceiling. Pre-installation and post-installation measurements would be collected via the Building Management System (BMS) by SGL Singapore Pte Ltd to observe the performance of the Chilled Ceiling. NTU would conduct another round of post-installation measurements using several data-logging sensors to further confirm the performance of the Chilled Ceiling. A thorough analysis of the measurements from the pre-installation and post-installation were conducted. Results have shown that the concept of Chilled Ceiling is feasible for use in Singapore as it was capable of providing thermal comfort. Even though the supply air was deliberately reduced to minimum level, no condensation is observed. Due to the deliberate reduction in supply air to prove the Chilled Ceiling concept, the indoor air quality was compromised as high level of Carbon Dioxide was observed which indicated inadequate indoor air ventilation. Due to the size of the test bed, an accurate analysis of the Chilled Ceiling financial viability was unachievable. Although results has shown a conservative 30.77% energy savings compared to conventional Fan Coil Unit (FCU), the fixed investment cost of the Chilled Ceiling was too significant for such a small test bed. Since the feasibility of the Chilled Ceiling concept has been proven in this test bed, a larger test bed with a size of at least 1000m^2 can be conducted in future to accurately analyse the financial feasibility of the Chilled Ceiling in Singapore.